Morphological and Molecular Assessment of Pentastomes from Gulls in Portugal - Literák, Ivan; Casero, María; Koubková, Božena; Těšínský, Miroslav; Heneberg, Petr (The Journal of parasitology, 2017)
During 2016, 153 gulls, including 64 Larus fuscus and 89 Larus michahellis, were found crippled in south Portugal. They died in Wildlife Rehabilitation and Investigation Center-RIAS and were necropsied. Reighardia sternae infected 2 (3%, n = 64) L. fuscus and 4 (4%, n = 89) L. michahellis. Molecular analysis confirmed the morphological identification on the basis of total body length, maximum body width, length of anterior and posterior hooks, total length of oral apparatus, and other features of oral apparatus of R. sternae. Both sequenced individuals in this study displayed 100% sequence identity to R. sternae individuals obtained previously from Larus ridibundus in Spain and to Reighardia sp. from Larus belcheri in Peru. Reighardia sternae is reported here for the first time in L. michahellis and for the first time from Portugal.
Keywords: Animals; Charadriiformes; Base Sequence; RNA, Ribosomal, 18S; ribozomální DNA; Female; DNA, Ribosomal; Electron Transport Complex IV; Portugal; ženské pohlaví; Bayesova věta; pravděpodobnostní funkce; respirační komplex IV; nemoci ptáků; Parasitic Diseases, Animal; Bayes Theorem; Likelihood Functions; Bird Diseases; parazitární nemoci u zvířat; konsenzuální sekvence; Sequence Alignment; RNA ribozomální 18S; Pentastomida; Consensus Sequence; sekvence nukleotidů; zvířata; Portugalsko; sekvenční seřazení